Contractor's entitlement to recover loss of profit on omitted works / [electronic resource] - Nurizzati Tukimin, 1989-, author, 609959 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2016